Power-limited spectral amplitude coding OCDMA system using random diagonal code with and without optical amplifiers - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid; R. Badlishah, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org